Human expertise and artificial intelligence in vertical search - Jackson, Peter (O'Reilly Media, 2011)
"Our talk summarizes some recent thinking in the field of vertical search and illustrates it in the context of a new version of Westlaw, called WestlawNext. We argue that getting the right allocation of function between person and machine is the key to making specialist content more findable and search results more understandable."--Resource description page.